Growth and structure of heteroepitaxial lead titanate thin films constrained by miscut strontium titanate substrates - Ichikawa, Y.; Matsunaga, T.; Hassan, M.; Kanno, I.; Suzuki, T.; Wasa, K. (Materials Research Society, 2006)
Single-crystal lead titanate (00l)PbTiO(3) (PT) thin films were heteroepitaxially grown on a miscut strontium titanate (001)SrTiO(3) (ST) substrate by radio frequency magnetron sputtering. The PT thin films were grown via a step-flow growth. The step-flow growth enhanced the layer growth resulting in the continuous (001) single-crystal structure without a dislocated interface for the film thickness below 200 to 250 nm. The PT thin films show a small temperature variation of the lattice parameters unlikely to the bulk PT crystals due to the substrate clamping. The temperature variation of the lattice constants is discussed in terms of the thermo-elastic deformation analysis for the PT/ST heterostructure.